Hashimoto's thyroiditis, vitiligo, anemia, pituitary hyperplasia, and lupus nephritis—A case report of autoimmune polyglandular syndrome type III C + D and literature review - Sun, Yongmei; Kan, Xuan; Zheng, Rongxiu; Hao, Liping; Mao, Zongtao; Jia, Ying (Frontiers in Pediatrics, 2023)
Objective: To summarize the clinical characteristics of one teenager with autoimmune polyglandular syndrome (APS) typeⅢA+C+D，in order to improve the understanding of APSⅢA+C+D and the effect of thyroid function. Methods: This article reported the clinical manifestations, laboratory examinations, treatment and outcomes of an adolescent with anemia admitted to the Pediatrics Department of Tianjin Medical University General Hospital in July 2020, and reviewed the literature. Results: A 13-year-old and 1-month-old girl was admitted to the hospital due to the discovery of anemia for more than 4 years and episodic abdominal pain for 1 week. 4 years ago, the girl went to a local hospital for "Vitiligo", and routine blood test revealed anemia. The lowest hemoglobin (HGB) was 61g/L, the blood test showed iron deficiency anemia. And she had no menstrual cramps for 2 months. Urine routine showed protein3+～4+, 258 red blood cells(RBCs)/ high-power field (HPF). Urine protein was 3380mg/24h. Free thyroxine was low, thyroid-stimulating hormone (TSH)> 100uIU/mL, thyroid peroxidase Antibody> 1000IU/mL, thyroglobulin antibody and thyrotropin receptor antibody were negative. Pituitary magnetic resonance imaging showed a mass in the sellar region with uniform signal and a maximum height of about 15.8 mm. The result of anti-nuclear antibody was 1:80 homogeneous type, anti-dsDNA and anti-cardiolipin antibodies IgA and IgM were slightly higher. Thyroxine and iron were given for 1 month, menstruation resumed, and urine protein and RBCs decreased. After 5 months of treatment, free thyroid function, HGB, RBCs in urine and pituitary returned to normal. Later, renal biopsy showed the changes of focal proliferative glomerulonephritis, and the girl was diagnosed with lupus glomerulonephritis type IIIA. After 3 days of shock therapy with methylprednisolone, prednisone and mycophenolate mofetil and other treatments were administrated for 1 year. At the time of writing, urine protein was 280mg/24h. Conclusion: Co-occurrence of Hashimoto's thyroiditis, vitiligo, anemia, pituitary hyperplasia and lupus nephritis is rare. It is very important to pay attention to the screening of thyroid function.